The effect of date palm extract and katuk leaves (sauropus androgynus) on breast milk production among breastfeeding mothers in the working area of midwife n’s private practice - Neng Suaidah; Irma Jayatmi; Ratna Wulandari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: One of the common problems experienced by postpartum mothers is low breast milk production. Sauropus androgynus (katuk leaves) and Phoenix dactylifera (dates) are known to contain galactagogue compounds that can stimulate prolactin and oxytocin hormones to enhance breast milk production. Purpose: To determine the effect of date extract and katuk leaves on increasing breast milk production among postpartum mothers in the working area of Midwife N Private Practice, Bandung Regency. Method: This research employed a quasi-experimental design with a two-group pretest-posttest approach. The sample consisted of two treatment groups, each comprising 10 respondents. The first group consumed 45 grams (3 tablespoons) of date extract once daily for seven days, while the second group consumed 100 grams of katuk leaves daily for seven days. Data was analyzed using paired sample t-tests and independent t-tests. Results:The results showed that the mean breast milk volume before consuming date extract was 4.3 ml and increased to 57 ml after the intervention, with a mean difference of 52.7 ml (p = 0.000). In the katuk leaf group, the average milk production increased from 4.9 ml to 68 ml, with a mean difference of 63.1 ml (p = 0.000). There was a significant difference between the two interventions (p = 0.000), indicating that katuk leaves had a greater effect on increasing breast milk production compared to date extract. Conclusion: There is a difference of date palm extract and katuk leaves in increasing breast milk production in postpartum mothers. Suggestion: It is recommended that postpartum mothers consume katuk leaves and date extract as natural alternatives to enhance breast milk production